Structural Elucidation of Oligosaccharides from Grewia oppositifolia seeds Galactomannan - Singh, R.B. (Asian Journal of Chemistry, 2010)
Partial acid hydrolysis of Grewia oppositifolia seeds galactomannan afforded O-α-D-galactopyranosyl-(1→6)-O-α-D-mannopyranose, O-β-D-mannopyranosyl-(1→4)-o-β-D-galactopyranose and o-β-D-mannopyranosyl-(1→4)-O-β-D-mannopyranosyl-(1→4)-O-β-D-mannopyranose.